A Newly Emerged Swine-Origin Influenza A(H3N2) Variant Dampens Host Antiviral Immunity but Induces Potent Inflammasome Activation. (11th June 2015) - Cao, Weiping; Mishina, Margarita; Ranjan, Priya; De La Cruz, Juan A.; Kim, Jin Hyang; Garten, Rebecca; Kumar, Amrita; García-Sastre, Adolfo; Katz, Jacqueline M.; Gangappa, Shivaprakash; Sambhara, Suryaprakash
Abstract : We compared the innate immune response to a newly emerged swine-origin influenza A(H3N2) variant containing the M gene from 2009 pandemic influenza A(H1N1), termed "A(H3N2)vpM, " to the immune responses to the 2010 swine-origin influenza A(H3N2) variant and seasonal influenza A(H3N2). Our results demonstrated that A(H3N2)vpM-induced myeloid dendritic cells secreted significantly lower levels of type I interferon (IFN) but produced significantly higher levels of proinflammatory cytokines and induced potent inflammasome activation. The reduction in antiviral immunity with increased inflammatory responses upon A(H3N2)vpM infection suggest that these viruses have the potential for increased disease severity in susceptible hosts.